English Language Teaching in Indonesian Primary Schools: A Review from the Perspective of Out-of-Field Teachers - Marcha Stephanie Inapratama Matitaputty; Meiti Leatemia (Jurnal Administrasi Terapan, 2025)
The inclusion of English in Indonesia’s primary education curriculum reflects a broader national effort to prepare students for global engagement. However, this policy initiative often collides with classroom realities, particularly in schools where English is taught by generalist or out-of-field teachers—those without formal qualifications in English language education. This literature-based study explores the pedagogical, emotional, and structural challenges faced by such educators, drawing from research published up to 2020. It reveals that out-of-field teachers often struggle with limited language proficiency, lack of methodological expertise, and diminished self-confidence, which results in textbook-dependent instruction and reduced communicative opportunities for learners. Despite these limitations, some teachers display resilience through informal peer learning, improvisation, and classroom innovation. Nevertheless, the mismatch between curricular expectations (as seen in Kurikulum 2013 and Kurikulum Merdeka) and teachers’ preparedness undermines instructional quality and learner outcomes. The study underscores the need for policy interventions that prioritize teacher training, ongoing professional development, and supportive school leadership. It concludes that the success of early English education hinges not solely on curriculum design, but on the capabilities, confidence, and well-being of the teachers tasked with delivering it.Keywords: out-of-field teaching, primary English education, Indonesia, teacher identity, curriculum implementation, teacher preparedness, pedagogical challenges.